Cultural Literacy as Conflict Mitigation of Sampit Dayak and Madurese Muslims in Tanah Mas Sampit Indonesia - Gita Anggraini (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Tanah Mas is one of the areas in Sampit that the Sampit Dayak and Madurese Muslim communities inhabit. They live side by side, peacefully exchanging culture and language. This area's uniqueness needs to be explored further so that it can become a good practice for mitigating conflicts that often occur in Indonesia. This study explores the cultural values developed, the processes of exchange and cultural literacy, and the cultural literacy methods used in Tanah Mas. The research was conducted using qualitative methods with an ethnographic approach. The research was conducted for two months. The research locus was Tanah Mas Village, Baamang Sampit District. The study results show that cultural literacy is carried out in the family, community, and leaders. Parents provide examples and advice in the family to live well together and get along with anyone regardless of ethnicity. Community leaders provide examples and advice to respect each other, help each other, and cooperate reasonably with each other. Social literacy is performed by performing arts conveying messages of peace and moral teachings. In addition, the community mingles and cooperates in various activities. Information exchange is carried out through daily activities such as community interaction, traditional events such as weddings, religious events such as the Prophet's birthday or isra' mi'rāj, and artistic activities such as art performances.